Star wars, Thrawn [compact disc, unabridged] - Zahn, Timothy (Zahn, Timothy. Star wars., 2017)
Traces the origins of Thrawn, one of the most ruthless warriors in the Galactic Empire, and the events behind his rise in the Imperial ranks.